Strategic Public Relations Management: Bridging Madrasas and External Stakeholders for Educational Excellence - Christiyanto, Tedy; Munandar, Aris; Hilmi, Hilmi (JURNAL AL-TANZIM, 2026)
This study aims to analyze public relations management in strengthening external institutional collaboration in madrasas. This research uses a qualitative case study approach, with data collected through interviews, observation, and documentation. Data analysis was conducted through three main stages: data reduction, data presentation, and conclusion drawing/verification. The results indicate that public relations management plays a strategic role in facilitating collaboration through structured planning, organizing, implementing, and controlling mechanisms based on the POAC (Planning, Organizing, Actuating, and Controlling) principles. This institutional collaboration contributes to improving educational programs, student activities, and the madrasah's institutional support system. However, the implementation process still faces several obstacles, particularly limited human resources and ineffective communication practices. Nevertheless, the results of the established collaboration indicate increased stakeholder participation, strengthened institutional support, and easier access to external resources that support educational development. This study suggests that a structured public relations management approach grounded in POAC principles can enhance the effectiveness of external collaboration, strengthen institutional support, and maximize stakeholder participation. Madrasas are advised to strengthen their human resource capacity and internal communication to optimize and sustain PR practices.